BIOLOGICAL ACTIVITIES, PHENOLIC CONSTITUENTS AND OF VARIOUS EXTRACTS OF CYCLAMEN COUM TUBERS AND LEAVES FROM TURKEY - Aydin, Cigdem; Mammadov, Ramazan; Davidov, Mahmudcon (Химия растительного сырья, 2023)
The present study evaluated thephenolics composition and biological activities of various extracts of Cyclamen coum. The antioxidant properties of these plant wasdetermined using the scavengingmethods (DPPH andABTS), total antioxidant test systems (β-carotene/linoleic acid), reducing power (FRAP) assays.The antibacterial effect was examined with MIC method. The phenolics were identified using HPLC and the brine shrimp lethality test was used to screen for possible toxicity. Larvicidal activity against Cx. pipienswas assessed.The highest phenolic compound was foundcinnamic acid with 411.6 µg/g. The highest total phenolic and flavonoid were found in the ethanolic extracts with 8.99±3.07 mgGAE/mL and 54.66±3.02 mgQE/g, respectively. The tuber-methanol extract exhibited the highest antioxidant capacity (β-carotene/linoleic acid test, 76.43±3.02%). The radical scavinging activity of the extracts varied from 129.74±0.02 (tuber ethanol) to 336.3±0.02 (tuber acetone) IC50 μg/mL (DPPH assay) and from 118.04±0.07 (tuber ethanol) to 321.96±0.08 (leaves acetone) IC50 μg/mL (ABTS assay). Very strong reduction of Gr (+) S. aureus growth were observed during incubation in tubermethanolic extracts (MIC was 56±0.03μg/mL). The brine shrimp lethality assay of tubermethanol extract has showed good cytotoxic with LC50 of 3.016 μg/mL. The tuber extract of C. Coum showed highest larvicidal activity against Cx. pipiens with value LC50 (296.80 μg/mL). C.coum could be a source to derive the potential antioxidant and cytotoxic agents. However, further studies are needed to determine the mechanism involved in the process.